On some related enumeration problems - Zatorsky, R.A.; Pylypiv, V.M.; Gulka, S. (Carpathian Mathematical Publications, 2013)
The article is devoted to enumeration of partitioning of some classes of multisets, $n$-vertex regular graphs of the second degree and bitransversals of $n$-th order.